Territórios do samba e relações intergeracionais: estilo de vida, sociabilidades e economia socioafetiva - Almeida Neto, Mateus Antonio de (2023)
The central objective of this Thesis is to propose a reading of youth, lifestyles and sociabilities from a bias of intergenerational relations, through the practice of listening, playing, producing, reproducing, consuming, circulating, exchanging and experiencing samba through the city of Aracaju, Sergipe, Brazil, as a practice of sociability, identity and economy linked to the sound memories of musical repertoires of the African diaspora, which are also configured as a practice of territorialization. I start from the idea that a part of the youth of diachronic generations of the globalized world, from contexts of peripheral neighborhoods, with markedly ethnic-racial and afro-descendant characteristics, build musical careers in favor of their autonomies, as a culture of resistance and social existence. These are forms of assemblages that permeate sociabilities, since knowledge about certain knowledge is transmitted from generation to generation, just like leisure, creativity and aestheticization in the face of precarious conditions historically experienced. The methodology used is that of field work, based on direct and participatory observation. I also use interviews, informal conversations, obedience and access to the official social networks of the “local samba” protagonists, as a resource to help me understand. Among the results, it was possible to observe that the taste for the samba genre is processed and re-signified in an intergenerational way, mainly through social and cultural exchanges between youths from peripheral territories, with markedly ethnic-racial and afro-descendant characteristics as a lifestyle. In addition, the musicality of samba is activated through creativity, aestheticization and sociability relations as an alternative for employability. That is, the process of autonomy in the face of the precariousness of work relationships is something that also implies the sharing of relational, disparate, changing and hybrid musical trajectories between different generations.____________________________________________________________________